KRITIK KH. AHMAD DAHLAN TERADAP PENDIDIKAN ISLAM DAN KAITANNYA DENGAN PENDIDIKAN NASIONAL - enok sadiah (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
AbstractEducation has an important role in building quality human resources (HR). K.H Ahmad Dahlan stated that a good education is education that meets the needs of the times. This study discusses the perspective of KH. Ahmad Dahlan on Islamic education in Indonesia, and the relevance of Ahmad Dahlan's critique of Islamic Education in the colonial era with today's national education. The method used by the researcher is a literature review by identifying theories, as well as the results of previous studies which are then identified so as to obtain the results of the researchers' exploration achievements. After conducting a study on the perspective of KH Ahmad Dahlan regarding Islamic education and its relation to national education, the relationship between Islamic education and national education is an inseparable unit. There are several problems that arise during the implementation of national education, including the occurrence of an educational dichotomy and curriculum changes.